Teknik Meningkatkan Pengelolaan Credit Union terhadap Perbankkan dengan Memanfaatkan Teknologi Online - M Maran; Widya Dharma (Jurnal Teknologi, 2021)
Savings are generally embedded and accumulated in the long term in a bank. Savings in this study are public deposits that accumulate in the long term and receive remuneration in the form of interest, which is popular among Credit Unions (CU) with the term deposit remuneration. Savings or deposits in CU need to be studied more deeply. Savings in CU is one solution to save for the poor, and do not have access to banking institutions. In this study, we want to know the impact of interest rates, Regional Gross Domestic Product (GRDP) growth per capita, inflation rates and economic growth on savings or deposits in CU, in West Kalimantan. This study uses the associative method with multiple linear analysis techniques, using secondary data, from 19 CUs in West Kalimantan, with a period of 2009 to 2019. Our results show that deposit interest rates, per capita income, inflation rates and economic growth simultaneously affect savings. or savings in CU, but the effect is very small. Partially, deposit interest rates, per capita income, inflation rates, and economic growth have no effect on the development of savings or deposits in CU in West Kalimantan.